Recognition of Palestinian Statehood: A Clarification of the Interests of the Concerned Parties - Haddad, Aitza M (2012)
This paper reviews the history of the claims to statehood and sovereignty of the Palestinian people, from the period of the League of Nations mandate to the current move to secure UN approval of a Palestinian State. The article examines the claims to statehood in international law and examines the problem in the broader context of claims about human rights and humanitarian violations, the Israeli claims to security and legitimacy and the US claims for its mediation goal to ensure that the problem does not descend into a legal vacuum in which the fundamental interests of all parties in security and essential dignity are destroyed. It reviews the ideological motives of the current Israeli regime in light of the complexity for the Obama administration in establishing preconditions for a negotiated settlement. The article considers the implications of the recognition of sovereignty on these continuing issues. This paper is an expanded version of one delivered at the British section of the International Law Association, annual conference in Sheffield, England (April 2011)